Functional Outcome of Post Anterior Cruciate Ligament Reconstruction Patients in Dr. M. Djamil Central General Hospital Padang 2020-2022 - Rinaldiansyah; Rahmadian, Rizki; Fortuna, Fory; Eka Sahputra, Roni; Ramda Ilhami, Yose; Renita Rusjdi, Selfi ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2025)
Background: The anterior cruciate ligament (ACL) is the main stabilizer of the knee joint. The incidence of ACL injuries is quite high, especially in individuals who participate in sports. ACL injuries result in knee instability, hindering daily activities and sports participation. This study aimed to determine the functional outcomes of patients who have undergone ACL reconstruction. Methods: This study was descriptive, with a cross-sectional approach, and used medical record data from Dr. M. Djamil Central General Hospital Padang. The total sampling technique was used from patients after ACL reconstruction in 2020-2022. Patients with bilateral knee injuries, multiple ligament injuries, or revision reconstruction were excluded from the study. The samples were contacted to determine their functional outcome by filling out the Lysholm Knee Score. Results: This study analyzed 27 patients, with 77.8% in the 19-44 age group, and no patients were over 60 years old. This study identified 85.2% of male patients with sports-related injuries being the most common (70.4%). The non-dominant knee was injured more frequently (51.9%). Functional outcomes, as assessed by the Lysholm Knee Score, showed excellent, good, and moderate results in 37 %, 29.6%, and 33.3% of patients, respectively. Conclusions: ACL reconstruction was most frequently performed in the adult population aged 19–44 years, predominantly in males. Sports-related injuries were the primary cause, with the majority of reconstructions involving the non-dominant knee. The average patient achieved good functional outcomes after ACL reconstruction.